Hubungan Kondisi Lingkungan Fisik Rumah Dengan Kejadian Tuberkulosis Paru Di Jawa Barat (Analisis Data Riskesdas 2013) - Ahmad Zacky Anwary; Lutfan Lazuardi; Mubasysyir Hasanbasri; Faisal Mansur; Bagian Prodi Kesehatan Masyarakat, FKM UNISKA; Bagian Prodi S2 Ilmu Kesehatan Masyarakat, Fakultas Kedokteran UGM; Bagian PKMK, Fakultas Kedokteran UGM (HB PRESS, 2016)
Tuberculosis (TB) is one of the pulmonary infectious diseases become a global threat, given the number of occurrences of cases, especially in Indonesia as one of the countries included in the 22 countries with major problems of tuberculosis disease (high-burden countries). Besides being the source of transmitting, one of the factors that can also affect the occurrence of pulmonary TB disease is the house physical environment (such as ventilation, natural lighting, flooring, and density of residential house) that does not qualify as a healthy home. Including the type of observational research with cross sectional study design. The target population is the population in West Java and the household members aged 15 years and above who became suspected pulmonary TB patients were successfully recorded/interviewed in Riskesdas 2013. There are some physical house environment variables significantly associated with the incidence of pulmonary TB in West Java that is the kitchen ventilation variable with an Odds Ratio (OR) of 1160, family room ventilation variable with OR 1.122, badroom natural lighting variable with OR 1148, and kitchen natural lighting variable with OR 1124. By knowing the variables that have a significant relationship to the occurrence of pulmonary tuberculosis so that people can pay more attention the efforts to improve the house physical environment into a better house.